BAKAIN DUO: Reaffirming The Symbols, Identity, And Sharia-Based Modesty (ʿAwrah) In The Attire Of Bundo Kanduang In Minangkabau - Sasmiarti, Sasmiarti; Busyro, Busyro; Manap, Norhoneydayatie Abdul (Hukum Islam, 2025)
Studies on women's aurat in Islam often focus on universal normative-theological approaches, thus ignoring the dynamics of locality and cultural symbolism. In Minangkabau, the traditional dress bakain duo worn by Bundo Kanduang contains complex symbolic meanings, but has not been interpreted in the frame of aurat verses. This research aims to reinterpret the bakain duo symbol as an articulation of identity, sharia, and culture in Minangkabau Muslim society. Using a qualitative approach and semiotic analysis, this study dialogues classical and contemporary interpretations of the aurat verses with local cultural narratives. The main literature includes works of Qur'anic tafsir, gender studies in Islam, and Minangkabau symbolic anthropology. The results of the discussion show that bakain duo is not only a symbol of traditional modesty, but also an expression of local interpretation of the Shari'ah of aurat that functions as a marker of female identity. The conclusion of this research emphasizes that local cultural symbols can be a medium of contextual interpretation.